1989
DOI: 10.1063/1.456672
|View full text |Cite
|
Sign up to set email alerts
|

The positive muon in the intermetallic hydride ZrV2Hx: A muon tracer study supplemented by differential thermoanalysis, neutron vibrational spectroscopy, and quasielastic neutron scattering

Abstract: ChemInform Abstract (phase diagram, structural and dynamical properties of the ZrV2/H system).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 42 publications
4
25
0
Order By: Relevance
“…In this alloy muon is found [13] static up to 50 K. For T > 50 K, the muon diffuses in a tunnelling process and over 50-250 K the under-barrier jump rate for muon diffusion is described by the formula This result can be explained by the present theory which assumes the tunnelling of muon under a potential barrier (H). Using the potential barrier for hydrogen diffusion (Hp ) = 1000 K [14] and considering the isotopic reason, H is set equal to 1000 K. Then for b = 3 Å, β becomes 2.3 x 10-6 .…”
Section: Zrv2supporting
confidence: 60%
“…In this alloy muon is found [13] static up to 50 K. For T > 50 K, the muon diffuses in a tunnelling process and over 50-250 K the under-barrier jump rate for muon diffusion is described by the formula This result can be explained by the present theory which assumes the tunnelling of muon under a potential barrier (H). Using the potential barrier for hydrogen diffusion (Hp ) = 1000 K [14] and considering the isotopic reason, H is set equal to 1000 K. Then for b = 3 Å, β becomes 2.3 x 10-6 .…”
Section: Zrv2supporting
confidence: 60%
“…measurements at high energies (24). The situation is different for acoustic phonons, which occur at low energies with the effective mass dominated by the metal atoms (25).…”
Section: Resultsmentioning
confidence: 98%
“…Finally, we considered whether the peak is associated to hydrogen vibrations in pure vanadium. Under certain conditions (24), ZrV2Hx can segregate into a Zr-rich alloy and VHx phases. The dominant feature of INS of VHx is around 55 meV (26) (SI Appendix, Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Then for the barrier width b=0.5 Å , the barrier transparency coefficient β becomes 10 -2 . Therefore the jump rate formula becomes This formula finds a good comparison to the experimental values at temperatures above 300 K. Muon diffusion in ZrV2Hx has been studied over the temperature range 2-250 K [18]. In this study muon in found to remain immobile for T < 50 K above which the muons start to diffuse.…”
Section: Yh2mentioning
confidence: 89%